The impact of economic-related freedoms on the national entrepreneurial activity - Juan M. Dempere; Alexandrina Maria Pauceanu (Journal of Innovation and Entrepreneurship, 2022)
This article aims to analyze the explanatory power of the constituent components of the Heritage Foundation's Index of Economic Freedom over the Global Entrepreneurship and Development Institute's Global Entrepreneurship Index and its sub-indexes. We analyze a sample of 118 countries with available historic data from 2014-2019. We evaluate the impact of the business, labor, monetary, trade, investment, and financial freedom indexes over the Global Entrepreneurship Index and its sub-indexes. We performed a cross-sectional analysis using generalized linear models and weighted least squares models. We also analyzed our panel data using panel-corrected standard error models. We find a significant and positive relationship between the Global Entrepreneurship Index and the business and financial freedom indexes. We also find a significant and positive relationship between the business and financial freedom indexes and the entrepreneurial attitudes, abilities, and aspirations sub-indexes. The limitations of our study include the diversity of national entrepreneurial ecosystems and the difficulty of measuring them with a few quantitative variables. Additionally, our results are heavily influenced by the selection of countries in our sample. To the best of the authors' knowledge, no previous research article has studied the explanatory power of the Index of Economic Freedom's constituent components over the Global Entrepreneurship Index and its sub-indexes. Similarly, our sample of 118 countries with data from 2014-2019 makes our study the most comprehensive global analysis about the relationship between economic freedom and entrepreneurship so far.
Keywords: 650; Economic freedom; Entrepreneurial ecosystems; Global Entrepreneurship Index; Index of Economic Freedom; Necessity entrepreneurship; Opportunity entrepreneurship